Identification of novel interactions between MicroRNAs and pattern-recognition receptor signalling in dentritic cells - Pichulik, T (2011)
Dendritic cells are equipped with a range of different pattern-recognition receptors (PRR) aimed at recognizing foreign pathogens. Recent evidence has suggested that PRR signalling regulates the expression of microRNAs (miRNAs), important post-transcriptional regulators of gene expression, which have been shown to fine-tune innate immune responses. This thesis describes the discovery of miR-650, a novel PRR-responsive miRNA that is down regulated in monocyte-derived dendritic cells (DCs) on PRR stimulation. Chapter 4 describes the characterisation of miR-650 expression in DCs matured by exposure to a variety of different pathogen-derived ligands, or during Influenza A virus infection. When correlating the level of miR-650 to the induction of DC activation markers on the cell surface, an inverse correlation was observed, suggesting a relationship between miR-650 down regulation and the effective dose of the ligand. Work presented in this thesis further explores the potential function of miR-650 by using a multi-pronged approach encompassing computational biology, genome-wide expression profiling and individual reporter assays, to gain insight into the gene networks regulated by miR-650. While Chapter 5 focuses on the identification and confirmation of individual miR-650:target interactions, Chapter 6 investigates both direct as well as secondary effects exerted by miR-650 on a global level. The work in these two chapters identifies a number of novel miR-650 targets and suggests a dual role for miR-650 in the innate immune response. Firstly, it is shown that miR-650 directly regulates a group of interferon-stimulated genes with known antiviral activity. Supporting its role in antiviral host defence, miR-650 is also shown to directly target components of the autophagic machinery, and even more importantly, down regulation of miR-650 induces autophagosome formation. Secondly, identified targets also include negative regulators of innate signalling suggesting that, in addition to its antiviral function, PRR-mediated down regulation of miR-650 expression may also provide a negative feedback loop controlling inflammatory responses. Notably, miR-650 displays reciprocal target regulation with miR-155, a well-studied miRNA with established functions in the innate immune system, thus suggesting cooperativity between the two miRNAs. The original aim of this thesis was to examine the effect of HIV-1 infection on the global miRNAome of DCs using a genome-wide profiling method. However, as outlined in Chapter 3, the data generated suggest that HIV-1 infection has little or no impact on miRNA expression. Further work is needed to establish if this represents deliberate immune evasion by HIV-1, or just indicates the limits of the methodology employed.